Uji Efektivitas Pestisida Nabati Ekstrak Daun Pepaya (Carica papaya L.) dan Ekstrak Ubi Gadung (Dioscorea hispida Dennst) pada Mortalitas Penghisap Buah Kakao (Helopeltis spp.) - Azhari, Dryantama; Sudirman, Albertus; Maryanti, Maryanti (Jurnal Agro Industri Perkebunan, 2022)
Fruit-sucking bugs (Helopeltis spp.) are one of the main pests on cocoa plants. The damage caused by this pest is by piercing and sucking the liquid of cocoa pods and young shoots. This study aimed to obtain the effective concentration of papaya leaf extract and yam extract on the mortality of cocoa fruit-sucking bugs. This research was carried out at the Plant Production Laboratory II of the Politeknik Negeri Lampung from September 2020 to January 2021. The design used in this study was a Randomized Block Design consisting of 4 treatments and six replications. The results showed that the average daily mortality rate fluctuated in each treatment. In all treatment concentrations of papaya leaf extract and yam extract, the average mortality of cocoa fruit-sucking bugs ranged from 25.76% to 75.76%. All treatment concentrations of papaya leaf extract and yam extract were not effective in the mortality of cocoa fruit-sucking bugs.